A pharmacokinetic, pharmacodynamic, and safety study of intravenous cyclophosphamide with an oral casopitant antiemetic regimen in cancer patients. Issue 2 (25th September 2013) - Adams, Laurel M.; Johnson, Brendan; Murray, Sharon
Abstract Casopitant is a potent and selective neurokinin‐1 receptor antagonist formerly under development for a number of indications, including the treatment of chemotherapy‐induced nausea and vomiting. This study was an open‐label, randomized, multi‐center, two‐period crossover casopitant–cyclophosphamide interaction study. Subjects were cancer patients receiving cyclophosphamide based chemotherapy. The objectives of the study were to assess the effect of 3‐day, repeat‐dose, 150 mg oral casopitant on the pharmacokinetics (PK), safety, tolerability, and pharmacodynamics (white blood cell count) of single‐dose IV cyclophosphamide. PK data from 14 evaluable subjects showed the geometric least‐squares mean ratios (90% CI) for cyclophosphamide and the metabolite 4‐hydroxycyclophosphamide AUC (with:without casopitant) were 1.03 (0.975, 1.09) and 0.948 (0.835, 1.08), respectively. Administration of casopitant was well tolerated and did not impact the safety profile of the treatment regimen. Casopitant did not affect the expected bone marrow toxicity of cyclophosphamide. Co‐administration of 150 mg oral casopitant with single‐dose IV cyclophosphamide did not appear to result in a clinically relevant change in cyclophosphamide or 4‐hydroxycyclophosphamide exposure or safety.